2014
DOI: 10.2215/cjn.01680214
|View full text |Cite
|
Sign up to set email alerts
|

Familial Clustering of ESRD in the Norwegian Population

Abstract: Background and objectives Studies and clinical experience suggest that kidney disease clusters in families, but few population-based studies have been performed. This study investigates risks and causes of ESRD in Norwegians with and without a first-degree relative with ESRD.Design, setting, participants, & measurements On the basis of data from the Norwegian Population Registry, firstdegree relatives for most Norwegians were identified. All Norwegians with ESRD (defined as chronic RRT) since 1980 have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 23 publications
2
61
0
1
Order By: Relevance
“…Alternatively, in the general population, we know that the blood relatives of patients with ESRD have an increased risk of developing ESRD. 7 Additional studies that provide longer follow-up for unrelated donors will be needed to understand this issue better.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, in the general population, we know that the blood relatives of patients with ESRD have an increased risk of developing ESRD. 7 Additional studies that provide longer follow-up for unrelated donors will be needed to understand this issue better.…”
Section: Discussionmentioning
confidence: 99%
“…Freedman et al [17] studied incident dialysis patients and found a 20% prevalence in a relative with ESKD. More recently, Skrunes et al [18 ]demonstrated that in a Norwegian ESKD population having a 1st-degree relative with ESKD conferred a 7-fold increase in the risk of developing kidney disease. However, few studies have examined both CKD and ESKD populations.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that there is a familial clustering of ESRD [24,25]. Skrunes et al found increased mortality in first-degree relatives of patients with ESRD [26]. Differentiating potential effects of donation from hereditary factors is a problem in donor studies, since most donors are closely related with the recipient, and most studies do not include enough unrelated donors to perform separate analyses in this group.…”
Section: Resultsmentioning
confidence: 99%